Research on Offset Phase Synchronization Method of Fan Drive Gearbox Planetary Gear - Jin Feng; Xiaofan Liu; Kun Qin (Jixie chuandong)
In order to support the development of the Geared turbofan （GTF） engine in China， the five-branch-power-split herringbone star gearbox for Fan drive gear system（FDGS） is studied. The manufacturing and assembling errors that affects the load sharing coefficient of the star gear system are analyzed. The calculation model for static load sharing coefficient of the star gear system is established. By calculating and analyzing the static load sharing coefficient of a star gear system test piece， the sensitivity of the manufacturing and assembling errors is obtained， the method of reducing the static load sharing coefficient by adjusting offset phase of star gears is proposed， and how to synchronize the eccentricity phase of planetary gear during assembly process illustrated by a star gear system test piece.